Corporate social responsibility as a factor in the formation of corporate culture: mechanism for ensuring sustainability and adaptability - Puchkov, О.; Kholodkov, Ye.; Пучков, О. О.; Холодков, Є. М. (Харківський національний автомобільно-дорожній університет, 2025)
This article is dedicated to the study of Corporate Social Responsibility (CSR) as an important factor in shaping a company's corporate culture, promoting sustainability and adaptability in the face of contemporary economic, social, and environmental challenges. The relevance of CSR is emphasized in the context of globalization and the increasing demands of stakeholders, including consumers, investors, and employees. The research proposes approaches to integrating CSR into corporate governance, identifying key elements of the mechanism aimed at strengthening corporate values, enhancing employee engagement, and ensuring the long-term competitiveness of companies in a dynamic external environment. A mechanism for integrating CSR into corporate culture is proposed, consisting of six interrelated stages: analysis of the current state, development and implementation of a CSR management system, integration into key business processes, communication and reporting, monitoring and performance evaluation, and ensuring CSR sustainability. Based on this integration process, a structural model for the formation of CSR has been developed, consisting of six interconnected blocks, each covering critical aspects of CSR implementation. The developed approach to understanding and implementing the CSR mechanism includes a staged process, influencing factors, and structural organization. An important aspect of the model is the integration of CSR into human resource management, corporate culture, and stakeholder engagement. The significance of transparent reporting and communication in building trust and enhancing CSR effectiveness is highlighted. The need for constant monitoring and adaptation of CSR strategies to changing external conditions is emphasized. The integration of CSR into corporate culture contributes to the sustainable development of the enterprise, enhancing its reputation and competitiveness. The proposed CSR mechanism model allows companies to effectively adapt to changing conditions while maintaining a balance of economic, social, and environmental interests.
Корпоративна соціальна відповідальність як фактор формування корпоративної культури: механізм забезпечення сталості та адаптивності
Keywords: Corporate Social Responsibility; corporate culture; sustainable development; CSR mechanism; CSR integration; stakeholders; reporting; monitoring; корпоративна соціальна відповідальність; корпоративна культура; сталий розвиток; механізм КСВ; інтеграція КСВ; зацікавлені сторони; звітність; моніторинг; 334.72:005.3:658.3; 10.30977/ЕТК.2225-2304.2025.45.211